Nacional System of Tsunamis Monitoring - Chacón Barrantes, Silvia (2016)
Tsunamis can happen in any water body, more specifically in any ocean.Therefore, our country, having two coasts, is exposed to tsunamis. Tsunamiscannot be avoided or predicted more than a few hours before their arrival;therefore tsunami warning centers are necessary to mitigate the impact they canhave on coastal populations. In our country, only the National Commission ofRisk Prevention and Emergency Response (CNE) is authorized to issue warnings.For other natural hazards such as earthquakes and meteorological phenomena,the CNE bases its decisions on technical and scientific institutions that emittheir assessment accompanied by recommendations. Since 2007 the CNE hasconsulted several oceanographers when international tsunami warning centersissued information about possible tsunamis. However, until 2014 there was nota technical institution working on tsunamis specifically. In April this year, theNational Tsunami Monitoring System (SINAMOT) was founded to fill this gap.The SINAMOT analyzes information related to coastal earthquakes and issuesreports to the CNE, with indications of the level of danger and recommendations in each case. Additionally, the SINAMOT provides consultancy and training related with tsunamis, both to CNE and to other entities when prompted. The SINAMOT consists of two physical oceanographers from RONMAC Program and two marine engineers from the Unit of Maritime Engineering Rivers and Estuaries (IMARES) of the Research Institute of Engineering (INII) of the University of Costa Rica (UCR). The four members of SINAMOT are available 24/7 to address tsunami warnings. The SINAMOT has a monitoring room in the RONMAC Program in the Department of Physics a second monitory room it will soon be completed at IMARES for monitoring redundancy and ensure quick access to all its members.